1991
DOI: 10.1007/bf00551907
|View full text |Cite
|
Sign up to set email alerts
|

Residual stress effects and t ? m transformation in ion-implanted yttria-stabilized zirconia

Abstract: Ion-beam treatment affects the near surface region of ceramic materials and is a potential technology in altering the surface microstructure and properties, in this study, a preliminary surface modification in yttria-stabilized zirconia was investigated through the employment of ion implantation. Fracture toughness and hardness were measured and evaluated by the indentation method for specimens implanted by direct As + bombardment. With the aid of residual stress measurement by X-ray diffraction, the propertie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…These results indicate that a tetragonal to cubic ( t–c ) transformation took place after the specimens were exposed to 70 Gy irradiation and some theories may explain the mechanisms behind this transformation. A significant effect of ionizing irradiation on zirconia microhardness was reported as a result of residual compressive stresses generated by t – c surface phase transformation, confirming the findings of the present study (Duh & Wu, ). Besides the t–c transformation, the stress field associated with those changes can escalate to irradiation “defects” due to localized vacancies developed, as previously reported in a study investigating 10 mol% yttria‐stablized zirconia (Bekale et al, ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These results indicate that a tetragonal to cubic ( t–c ) transformation took place after the specimens were exposed to 70 Gy irradiation and some theories may explain the mechanisms behind this transformation. A significant effect of ionizing irradiation on zirconia microhardness was reported as a result of residual compressive stresses generated by t – c surface phase transformation, confirming the findings of the present study (Duh & Wu, ). Besides the t–c transformation, the stress field associated with those changes can escalate to irradiation “defects” due to localized vacancies developed, as previously reported in a study investigating 10 mol% yttria‐stablized zirconia (Bekale et al, ).…”
Section: Discussionsupporting
confidence: 91%
“…(Fabris, Paxton, & Finnis, ; Guo, ; Karapetrova et al, ) For example, it was observed that by controlling the concentration of oxygen vacancies tetragonal phase can be stabilized at room temperature. (Duh & Wu, ) Therefore, monoclinic‐to‐tetragonal, and tetragonal‐to‐cubic phase transformations can be triggered by increasing the oxygen vacancy concentration. (Badwal, Bannister, & Hannink, ) This correlation between oxygen vacancy and the phase stability of zirconia has also been shown in other studies (Eichler, ; Guo, ).…”
Section: Discussionmentioning
confidence: 99%
“…This is because the glass penetrates the grain boundaries and gradually separates the ceramic grains, leading to an increase in volume accompanied by localized compressive stresses at the surfaces of graded materials. We are currently conducting residual stress measurements of graded structures by micro-x-ray analysis using the “sin 2 ψ ” technique [48, 49]. Preliminary results have revealed no significant residual stresses at the graded glass-zirconia surface or in the center of the zirconia core, suggesting that the strengthen effect is indeed induced from the surface grading.…”
Section: Discussionmentioning
confidence: 99%